Where the mountain meets the moon - Lin, Grace (New York Little, Brown, 2011)
Minli, an adventurous girl from a poor village, buys a magical goldfish, and then joins a dragon who cannot fly on a quest to find the Old Man of the Moon in hopes of bringing life to Fruitless Mountain and freshness to Jade River.
Companion book to: Starry River of the Sky.
Companion: When the sea turned to silver.
Newbery Medal Honor Book, 2010.
Keywords: Fairy tales; Dragons -- Fiction; Moon -- Fiction